Biobanks in the era of personalized medicine: objectives, challenges, and innovation: Overview - Kinkorová, Judita (The EPMA journal, 2015)
Biobanks are an important compound of personalized medicine and strongly support the scientific progress in stratification of population and biomarker discovery and validation due to progress in personalized medicine. Biobanks are an essential tool for new drug discoveries and drug development. Biobanks play an important role in the whole process of patient prevention and prediction, follow-up, and therapy monitoring and optimalization. Biobanks have the specificity in that they cover multidisciplinary approach to the human health combining biological and medical approaches, as well as informative bioinformatics technologies, computationing, and modeling. The importance of biobanks has during the last decade increased in variety and capacity from small collections of samples to large-scale national or international repositories. Collected samples are population-based, disease-specific or rare diseases originating from a diverse profile of individuals. There are various purposes of biobanks, such as diagnostics, pharmacology, or research. Biobanks involve, store, and operate with specific personal information, and as a consequence, such a diversity of biobanking is associated with a broad spectrum of ethical and legal issues. Biobanks are an international phenomenon because any single country, state, or society at the moment is not able to cover all issues involving the whole biobank problematic. Biobanks have an enormous innovative potential in the whole process of biomedical research in the twenty-first century.
Keywords: Definitions; History; Predictive preventive personalized medicine; Ethical and legal issues; Biobanks; Role of biobanks; Types